The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/brb3.1653
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‐345‐5p regulates depression by targeting suppressor of cytokine signaling 1

Abstract: Resistant depression (TED) is the most common mental illness (Sowa-Kućma et al., 2018). About 350 million patients have become a serious public health problem all over the world (Cusin et al., 2017). Studies have shown that TED is also associated with other diseases, such as osteoporosis, diabetes, and cerebral ischemia (Grønli & Wynn, 2013; Nierenberg, Mcintyre, & Sachs, 2015). Even so, the researchers' understanding of depression is still very limited. In recent years, people have found the structural change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Interestingly, we found that this specific region of circCARHSP1 is targeted by miR-24-3p and miR-345-5p. Notably, miR-24-3p regulates neuronal differentiation and promotes neurite growth [ 75 , 76 ], while miR-345-5p controls viability of microglia cells and represents a promising biomarker of the progression of C9orf72-associated disease [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found that this specific region of circCARHSP1 is targeted by miR-24-3p and miR-345-5p. Notably, miR-24-3p regulates neuronal differentiation and promotes neurite growth [ 75 , 76 ], while miR-345-5p controls viability of microglia cells and represents a promising biomarker of the progression of C9orf72-associated disease [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The apoptosis of microglia was evaluated using an Annexin V-FITC/PI apoptosis detection kit (BD Biosciences, CA, USA) via flow cytometry analysis [ 38 ]. After washed with phosphate buffered saline, microglial cells with indicate treatments were resuspended in binding buffer and then stained with Annexin V-FITC (5 µL; 10 min) and propidium iodide (PI) (5 µL; 5 min) at room temperature in the darkness according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…miR-345-5p is a tumor-suppressive miRNA in pancreatic cancer progression [38]. miR-345-5p induces inflammatory damage in hippocampal neurons [39] and has oncogenic roles [40]. miR-345-5p is also a promising blood-derived disease biomarker in multiple sclerosis [41].…”
Section: Lmcd1-as1 In Cholangiocarcinomamentioning
confidence: 99%